2015
DOI: 10.3349/ymj.2015.56.6.1632
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of the Right Para-Oesophageal Lymph Nodes in Papillary Thyroid Cancer

Abstract: PurposeAlthough guidelines indicate that routine dissection of the central lymph nodes in patients with thyroid carcinoma should include the right para-oesophageal lymph nodes (RPELNs), located between the right recurrent laryngeal nerve and the cervical oesophagus and posterior to the former, RPELN dissection is often omitted due to high risk of injuries to the recurrent laryngeal nerve and the right inferior parathyroid gland.Materials and MethodsWe retrospectively identified all patients diagnosed with papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…CLNM is common in DTC, with a frequency of 30-90% (17) and has been demonstrated to be closely associated with higher recurrence and poorer survival rates in patients with DTC (18). The majority of metastatic sites are located in central compartment lymph nodes, and complete central lymph node dissection has been identified to reduce the incidence of disease persistence, recurrence and mortality (19).…”
Section: Discussionmentioning
confidence: 99%
“…CLNM is common in DTC, with a frequency of 30-90% (17) and has been demonstrated to be closely associated with higher recurrence and poorer survival rates in patients with DTC (18). The majority of metastatic sites are located in central compartment lymph nodes, and complete central lymph node dissection has been identified to reduce the incidence of disease persistence, recurrence and mortality (19).…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 , 22 , 25 27 ] It has been reported that tumor size >1.0 cm was an independent predictor of LN-prRLN metastasis in patients with PTC. [ 12 , 27 ] Ito et al [ 28 ] reported that tumor size >2.0 cm was an important predictor of LN-prRLN metastases in patients with PTC in the right lobe. In the present study, LN-prRLN metastasis was more frequent in patients with tumor size >1 cm (20 of 32 cases, 62.5%), compared to patients with tumor size ≤1 cm (11 of 49 cases, 22.4%) ( P = .000).…”
Section: Discussionmentioning
confidence: 99%
“…According to this study and our clinical experience, we define the area posterior to the right RLN segment between laryngeal entry point and the intersection of the RLN with the innominate artery as the range of LN-prRLN dissection. Some researchers do not include the area above the level of the inferior thyroid artery in their LN-prRLN dissection to avoid injury of the right superior parathyroid and the associate blood supply [ 2 ]. However, this region usually includes some lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the incomplete resection of the lymph node posterior to the right recurrent laryngeal nerve in the first surgery can make the residual lymph nodes difficult to excise in the second surgery and even render the complete excision impossible. In this situation, patients who should have had a chance to be cured may thus lose the opportunity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%